"Development strategies at station areas in southwestern China: The case of Mianyang city". (November 2017) - Ortuño-Padilla, Armando; Espinosa-Flor, Aitor; Cerdán-Aznar, Lara
Highlights: Application of Node-Place model in an underdeveloped region Sichuan Province (China). Identification of possible redevelopments that restructure station areas. Field work is more necessary in this regions due to reliable data are not available. Abstract: This paper analyses the possibilities for implementing a TOD model around a railway station in Mianyang City, in southwestern China, through a Node-Place model to determine the potential for developing the areas around railway stations to foster a sustainable economic and urban development. For this purpose, the implementation of a TOD model means an interesting sustainable way for smart growth, whose successful implementation will strongly depend on the context, where the Growth Pole Theory is being implemented through the Western Development Strategy to strengthen the Chengdu-Chongqing Economic Zone. The Hukou system (household registration) and the current rapid urbanization and motorization trends are featuring the economic growth, creating inequities among urban population, informal settlements and problems in the accessibility of low-income residents. Therefore, not only does it lead to an analysis of the most important station areas in northeastern Sichuan Province but also of the socio-economic trends of one of the most underdeveloped regions of the country, yet with a high potential to be developed. Consequently, the real situation of the Northeast of Sichuan province is studied through fieldworks which complement the lack of reliable information, determining the most suitable features for achieving the best urban planning solution.